Real time durability of tribofilms in the piston ring – cylinder liner contact. (September 2017) - Spiller, S.; Lenauer, C.; Wopelka, T.; Jech, M.
Abstract: In boundary lubrication, the ability to form protective tribofilms determines the effectiveness of lubricants regarding friction and wear. In order to be able to control tribofilm formation, even if additives have to be reduced due to environmental regulations, the dynamics of the tribofilm protection of surfaces are investigated. This study investigates the durability of the tribofilm formed on the cylinder liner – piston ring contact and the corresponding wear protection capability in real time. To accomplish this, additivated engine oil was replaced by a non-additivated oil during test runs, after the steady-state wear rate had been reached. For the analysis of the tribofilm durability, the chemical composition of worn surfaces is compared to the dynamic wear and friction behavior. Highlights: Tribofilm durability after switching to unadditivated oil from fresh and aged oil. Formation of C-rich tribofilm when few or no additives present anymore. Lower steady-state wear rates and friction with C-rich tribofilm.